STRATEGI PENGELOLAAN KEUANGAN BAGI GEN Z DI ERA DIGITAL - Yuni Mayanti (DEVELOPMENT: Journal of Community Engagement, 2025)
Generation Z as digital natives, has extensive access to financial technology such as digital wallets, paylater, and investment apps. However, this is not always accompanied by adequate financial literacy, creating a gap between knowledge and daily financial management practices. The core problem for Gen Z in Mekarjaya Village is a lack of understanding of digital financial management and long-term investment instruments. This problem is further complicated by limited access to information and financial literacy materials and the lack of adaptation to local conditions. Therefore, this community service activity aims to raise awareness among Gen Z in Mekarjaya Village, Pacet, regarding the importance of financial management in today's digital era. The goal of this activity is to provide applicable solutions for Gen Z to become more financially literate and better manage their finances. The method used in this community service is Participatory Action Research (PAR). Evaluation results after participating in this activity indicate that Gen Z increasingly understands that financial management is very important to learn from an early age. Although Gen Z's financial resources are still limited, this socialization can serve as a foundation and principle for Gen Z to manage their future finances stably and prosperously.